Re-use of Industrial Heritage as a Tool of Conserving Urban Memory: Tirilye Olive Oil Factory - Acar Bilgin, Elif; Köprülü Bağbancı, Özlem (ICONARCH International Congress of Architecture and Planning, 2017)
Tirilye is a coastal settlement located in the west of Mudanya in Bursa, Turkey. Tirilye has been a hometown for Roman, Ottoman and Turkish people through centuries. Tirilye has a peaceful multicultural and multi-religious history with its churches, monasteries, a mosque, a hammam and traditional houses. There is an olive oil factory campus which built from 19th century to 1950s, embodies the technical equipment used in the olive oil production process that can be evaluated as an industrial heritage. Beside architectural context, industrial heritage also has a social and cultural way of understanding urban life. It is connected to human life directly, a work place and living place for citizens. This factory represents the development of olive oil production techniques and is a collective heritage of olive culture of Mediterranean people. Re-use of this factory can contribute to not only conservation of industrial heritage but also conservation of Mediterranean olive culture and urban memory of Tirilye. In this paper, the history and documentation of factory, definition as an industrial heritage, understanding the value, recommends for promotion and conservation studied in the context of preserving urban memory.